Evaluation of Magnetic Resonance Spectroscopy of The Brain: (Review of metabolites and clinical applications) - Al-Mahdi, Asia Mohamed et al. (University of Science and Technology, Sana'a, Faculty of Medicine and Health Sciences, Radiology and Medical Imaging Technology Program, 2023)
Magnetic resonance spectroscopy (MRS) provides unique information about the neurobiological substrates of brain function in health and disease. However, many of the physical principles underlying MRS are distinct from those underlying magnetic resonance imaging, and they may not be widely understood by neuroscientists new to this methodology. MRS conducts between good anatomic details presentation and accurate function of human organs and tissues. This review describes these physical principles and many of the technical methods in current use for MRS experiments. A better understanding for these principles and techniques may help investigators to accurate diagnosis for human diseases. For every case the image and spectrum presented and discussed according to its report and classification criteria to demonstrate the effect of MRS in diagnosis brain. This research based on descriptive method to demonstrate the effectiveness of MRS on diagnostic brain pathology. The result of this study show accurate diagnosis for brain using MRS.